Policy Analysis of Doubling Village Funds In Increasing The Number Of Prosperous and Superior Independent Villages - Judijanto, Loso; S Sumardi; Nurina, Lia; Nindy Puspitasari; Magisa, Nurul Septya (Universitas Pahlawan Tuanku Tambusai, 2023)
The two-fold policy of increasing superior and prosperous independent villages is a good policy for the village community economy and the national economy if managed and supervised well. However, if it is not managed and supervised properly, this policy will become easy food for corruptors and other priority projects will be hampered. This research is qualitative research with an explanatory approach. The data used in this research is secondary data that researchers obtained from scientific articles, books, journals and other credible sources. This data was collected using the stages of data collection, data selection, data reduction, and drawing conclusions. The research results show that the Village Fund Doubling Policy can improve independent villages that are superior, prosperous and prosperous. This policy can improve the Indonesian economy, improve the welfare of village communities, create independent villages and increase MSMEs originating from villages if managed well and closely monitored. However, if you don't have these two things, then this policy is a budget waste policy, easy food for corruptors, and hampers other projects. Keywords: Double, Village Funds, Prosperous and Superior Independent Villages